Dynamics of Communicative Norms in Modern Russian Speech - Клушина, Наталья Ивановна; Люликова, Анна Викторовна; Николаева, Анастасия Владимировна; Селезнева, Лариса Васильевна (Philology & Human, 2018)
The article reveals linguistic and communicative transformations in socially significant spheres of contemporary communication. The Internet genres, genres of media, advertising, business and professional communications are analyzed with the help of the historical and comparative method, methods of diachronic description and interpretation. It has been established that expressive lexis, the focus on dialogue, the freedom of self-expression and the equal status of communicators make the blog the most influential genre of the Internet communication. Owing to the influence of oral speech and corporate rules in the sphere of business communication a tendency towards agrammatism of phrases is getting increased. Professional communication is based on the interaction of communicative actors as a constructive dialogue in which emotionality, subjectivity and ethics are its main constitutive features. Innovations in the sphere of advertising communication are observed at the verbal level of the slogan and its implicit effect on the addressee.